Đánh giá hiện trạng và phân vùng cảnh báo nguy cơ trượt lở đất Thành phố Đà Nẵng - Hùng, Phạm Văn; Huyên, Nguyễn Xuân (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Landslide status evaluation and landslide hazard zonation for the Da Nang city The landslide occurence in the Da Nang city is strongly affected to the social-economic developent. - At least 110 landslide sites were detected during the last few years, among them 20 blocks are very large in size. The investigations are indicated that, the higher density of landslide is concentrated in the areas of Hoa Lien - Hoa Bac, Doc Kien - Ngam Doi (Hoa Phu) and Son Tra Peninsular. - The detailed study of landslide in different locations of the city allowed us to recognize the landslide generation that is closely related to the mair nine factors. Among the slope stability and rain fall rate are strongly correlated to a large portion of the landslide. The other factors such as the type of weathered crust, the characteristics of engineering geology, hydrogeology, fracture zone of the faults, etc... represent the different correlation with the landslide from location to the location. - The landslide hazard zonation map was created by the spatial analyses of all the mentioned above affected factors. The role of each factors was estimated from its relation to the landslide in the location and was expressed though the weighted value in the calculation scheme. - Four degree of landslide risks were separated for the landslide hazard map of the Da Nang city. The communes : Hoa Lien, Hoa Bac, Hoa Phu, Son Tra Peninsular and Hai Van pass are belonged to the very high and high landslide risk. The moderate landslide risks are found in the areas of midland : Hoa Chau, Hoa Phong, Hoa Khuong, Hoa Trung, Cam Le, Hai Chau and Ngu Hanh Son. The remain areas are accepted as the relatively stable zone in relation with landslide.